2017
DOI: 10.3354/dao03163
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of harbour seals Phoca vitulina to Brucella in declining populations across Scotland

Abstract: Since 2000 there has been a major decline in the abundance of Scottish harbour seals Phoca vitulina. The causes of the decline remain uncertain. The aim of this study was to establish the extent to which the seals in the regions of greatest decline have been exposed to Brucella, a bacterial pathogen that causes reproductive failure in terrestrial mammalian hosts. Tissues from dead seals collected between 1992 and 2013 were cultured for Brucella (n = 150). Serum samples collected from live capture−released seal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 56 publications
(55 reference statements)
0
10
0
Order By: Relevance
“…Several recent findings support the host role of the nematode in this infection. The highest prevalence of B. pinnipedialis infection in harbor seals, as determined by culture and serology, occurs after weaning and tends to decline with age (Lambourn et al 2013, Kershaw et al 2017. Results of a serologic survey of harbor seals in Alaska indicated seroconversion occurring between 4 and 8 mo of age (Hoover-Miller et al 2017).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several recent findings support the host role of the nematode in this infection. The highest prevalence of B. pinnipedialis infection in harbor seals, as determined by culture and serology, occurs after weaning and tends to decline with age (Lambourn et al 2013, Kershaw et al 2017. Results of a serologic survey of harbor seals in Alaska indicated seroconversion occurring between 4 and 8 mo of age (Hoover-Miller et al 2017).…”
Section: Discussionmentioning
confidence: 98%
“…With age, both lungworm infection and B. pinnipedialis infection decreases. Three surveys involving the culture of tissues from harbor seals found the lung to be the most frequently infected tissue, and it had the highest number of colony counts of any organ sampled (Lambourn et al 2013, Kershaw et al 2017, Kroese et al 2018. Lung and thoracic lymph nodes are not favored sites of predilection for terrestrial mammalian Brucella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Brucella infection is widespread in UK harbour seals; Kershaw et al (2017) found that 16% of a sample of 490 harbour seals tested positive for Brucella, although there were no pathological signs of infection. However, there was no evidence of higher sero-prevalence or circulating antibody levels in animals in the areas with the greatest declines.…”
Section: Other Diseasesmentioning
confidence: 98%
“…Sharples et al (2012) shown J o u r n a l P r e -p r o o f that harbour seals from Orkney had short duration trips at sea (~24-36h) in April and May (the sampling time of this study) therefore direct competition between inshore foraging seals and fisheries is likely. Other current hypotheses to explain the harbour seal decline include interactions with grey seals (Haelters et al 2012;Bouveroux et al 2014;Jauniaux et al 2014;van Neer et al 2015;Leopold et al 2015), killer whales (Orcinus orca) and infection by Brucella and exposure to harmful algae toxins (Kershaw et al 2017;SCOS 2018). Algal toxins may decrease prey quality of harbour seals such as plaice, whiting, and cod if these are contaminated (Jensen et al 2015).…”
Section: Scotlandmentioning
confidence: 99%